PENGGUNAAN MODEL PEMBELAJARAN NHT UNTUK MENINGKATKAN HASIL BELAJAR BIOLOGI KELAS XI IPA SMA ISLAM 1 PRAMBANAN TAHUN PELAJARAN 2009/2010 - Sumarjito, Sumarjito (UNIVERSITAS MUHAMMADIYAH METRO, 2011)
This classroom action research aims to determine the increase in student activity, where the learning process-centered and see an increase in student learning outcomes of biology in the 11th science class at The first Prambanan Islamic Senior High School in 2009/2010 academic year with learning models numbered heads together (NHT). The study consisted of two cycles, the first cycle had done by the two meetings held on 26 and May 27, 2010 with material